2012
DOI: 10.1002/art.33353
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ocrelizumab in patients with rheumatoid arthritis and an inadequate response to at least one tumor necrosis factor inhibitor: Results of a forty‐eight–week randomized, double‐blind, placebo‐controlled, parallel‐group phase III trial

Abstract: Objective. To evaluate the safety and efficacy of ocrelizumab plus methotrexate (MTX) or leflunomide (LEF) in patients with active rheumatoid arthritis (RA) and an inadequate response to tumor necrosis factor ␣ inhibitors.Methods. This was a multicenter randomized, double-blind, placebo-controlled, parallel-group study that continued over 48 weeks. Patients receiving stable doses of MTX or LEF were randomized to receive 2 infusions of placebo (n ‫؍‬ 277), ocrelizumab 200 mg (n ‫؍‬ 278), or ocrelizumab 500 mg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 47 publications
4
32
0
2
Order By: Relevance
“…obinutuzumab, ibrtumomab, ocaratuzumab) that could offer more potent depletion properties were considered but have either not started or advanced to larger scale trials in RA with the exception of the anti-CD20 antibody ocrelizumab which showed clinical efficacy in RA but was stopped due to increased infectious risk [55]. In contrast to complete B cell depletion a more subtle approach concerns inhibition of B cell modulatory cytokines.…”
Section: B Cells In Pathogenesis Ofmentioning
confidence: 99%
“…obinutuzumab, ibrtumomab, ocaratuzumab) that could offer more potent depletion properties were considered but have either not started or advanced to larger scale trials in RA with the exception of the anti-CD20 antibody ocrelizumab which showed clinical efficacy in RA but was stopped due to increased infectious risk [55]. In contrast to complete B cell depletion a more subtle approach concerns inhibition of B cell modulatory cytokines.…”
Section: B Cells In Pathogenesis Ofmentioning
confidence: 99%
“…[15] A phase III trial in rheumatoid arthritis enrolling patients receiving concomitant immunosuppressive medications (such as methotrexate or leflunomide) reported high rates of infections, especially with the 500 mg regimen, and some of those infections resulted in death. [85][86][87] There were no reported opportunistic infections in the phase II trial. Adverse events reported were similar between the treatment groups; however, there was one death in the 2000 mg arm.…”
Section: Monoclonal Antibodiesmentioning
confidence: 96%
“…Ocrelizumab is a fully humanized anti-CD-20 monoclonal antibody currently undergoing clinical trials in rheumatoid arthritis although its usage may be limited by an increased risk of infections in Asian patients receiving this therapy [49]. Biologic therapies are also potentially associated with an increased risk of one particularly severe side effect: progressive multifocal leucoencephalopathy (PML).…”
Section: Risks Of Using Biologic Therapies In Primary Sjögren's Syndrmentioning
confidence: 99%